MODELING THE AGRICULTURAL PRODUCTS MARKET DEVELOPMENT OF UKRAINE - BARNA, Marta; IVANIUK, Yurij (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The research is aimed at modeling the development of the market of agricultural products of Ukraine, using the Cobb-Douglas production function. This mathematical tool made it possible to analyze the interaction between labor (the number of employed workers) and capital (the cost of fixed assets) in the production process, considering the volume of agricultural products sold as a result of this interaction. The statistical data for the period 2013-2022, which were published by the State Statistics Service of Ukraine under section 01 “Agriculture, hunting and the provision of related services” of section A of the Classifier of types of economic activity KVED-2010, served as the information base for the modeling. It was determined that with an increase in capital and labor resources by λ times, the volume of sales of agricultural products will increase by λ0.195 times, which is characteristic of the developing Ukrainian economy. At the same time, the type of economic growth is dominated by intensive and labor-intensive economic growth of the market of agricultural products of Ukraine. The analysis of factors affecting the efficiency of production and sale of agricultural products in Ukraine indicated insufficient substitution between labor and capital. The value of the elasticities proved that in the constructed Cobb-Douglas production function, capital has a greater influence on production compared to labor. At the same time, a change in capital is accompanied by a more significant impact on production than a change in the amount of labor. The calculation of elasticity coefficients showed that a positive value of elasticity for capital indicates a direct relationship between capital and production, and a negative value of elasticity for labor indicates an inverse relationship between the amount of labor and production. Based on the construction of the equation of the isocline family, it was determined that in order to achieve the same volume of agricultural products, it is necessary to use a specific ratio between capital and labor, which is determined by the coefficient of 0.747. Understanding the impact of labor and capital on production allows agricultural enterprises to optimize the use of resources and predict market trends. Businesses can plan optimal combinations of labor and capital to achieve maximum productivity.